Place of endocrine-metabolic disorders in the development of endometrium pathology in climacteric women - Н. В. Косей; О. В. Занько; С. І. Регеда; О. О. Єфіменко (Publishing House TRILIST, 2019)
The results of a large number of studies indicate that the incidence of malignant transformation of hyperplasia endometrium increases significantly with age. Important in predicting the likelihood of hyperproliferative endometrial disease in postmenopausal women is a clear understanding of the causative factors that lead to pathological endometrium proliferation in the period of physiological decline of hormonal activity. Purpose of the study. To investigate the frequency and structure of somatic morbidity in women with hyperproliferative endometrial diseases in postmenopause and to determine the place of endocrine and metabolic disorders in the hyperproliferative pathology of endometrium development in this category of women. Materials and methods. Frequency and structure of extragenital morbidity, state of carbohydrate metabolism, lipid metabolism, leptin, estrone, prolactin, sex steroid binding protein, thyroid stimulating hormone and thyroxine levels we analyzed in 98 postmenopausal patients with morphologically confirmed forms of hyperproliferative pathology of endometrium (83 patients with endometrial polyps, 8 women with endometrial hyperplasia without atypia, 7 women with endometrial hypertension with atypia), and in 30 postmenopausal women with no changes in endometrium. Study results. Patients with hyperproliferative diseases had a higher incidence of dyslipidemia (64.28 vs. 20%), obesity (43.87 vs. 6.6%), arterial hypertension (40.81 vs. 26.6%), hypothyroidism (34.69 vs. 10%), and type 2 diabetes mellitus (18.36 vs. 3.3%) than in the control group (р <0,05). Average levels of estrone, leptin, HOMA index were also higher, and sex hormone binding globulin level was lower. Conclusions. Postmenopausal women with hyperproliferative endometrial diseases are characterized by elevated levels of extragenital morbidity and metabolic disturbances that are more common in women with endometrial hyperplasia with/without endometrial atypia than in women with endometrial polyps. Therefore timely diagnosis and treatment of endocrine-metabolic disorders will help to reduce the hyperproliferative pathology of endometrium in postmenopausal women.